THE IMPLEMENTATION OF CURRICULUM 2013 REVISION ON LESSON PLANS MADE BY ENGLISH TEACHERS OF SMAN 2 MAGELANG IN SCHOOL YEAR 2018/2019 - khurotul Aeini (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
ABSTRACTLesson plan helps the teachers organize the teaching and learning process. It is important to achieve the learning objective. Regulation of Ministry of National Education and Culture No 22 of 2016 is guidance to design the lesson plan. In fact, many teachers of SMAN 2 Magelang have not implemented the regulation in their lesson plan.There are two objectives of this research. First, it is to know the components of lesson plans made by English teacher. Second, it is to know how the implementation of curriculum 2013 revision in the lesson plans made by English teachers of SMAN 2 Magelang is.This research is descriptive qualitative. In conducting this research, the writer collected the documentation of 18 lesson plans made by 4 English teacher of SMAN 2 Magelang. The data were analyzed by using checklist then described.There are two results on this research. First, there are 13 components on lesson plans made by English teachers of SMAN 2 Magelang. Second, the implementation of components in lesson plans are different from one teacher to another. The average implementation of components in lesson plans made by teacher 1 is 98.46%, made by teacher 2 is 100%, the average implementation of components in lesson plans made by teacher 3 is 96.92%, and made by teacher 4 is 60%.According to findings, it can be concluded that the lesson plans made by 4 English teachers implement the components. The components are based on the Regulation of Ministry of National Education and Culture No 22 of 2016. According to the result above, the writer suggests to the teachers to complete the lesson plans and increase their knowledge especially in designing a lesson plan.Keyword: Lesson plan, Curriculum 2013 revision, English teacher